2002
DOI: 10.1183/09031936.02.01342001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tracheotomy on respiratory mechanics in spontaneously breathing patients

Abstract: Tracheotomy is a method of intubating the trachea, which is employed in several clinical settings, including the treatment of head and neck neoplasms. Tracheotomy is believed to facilitate weaning through changes in respiratory mechanics. Existing information concerning functional changes associated with tracheotomy are limited to comparisons with orotracheal intubation.In this study, respiratory mechanics were monitored in seven spontaneously breathing patients, before and after an elective tracheotomy was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 17 publications
(13 reference statements)
0
23
0
3
Order By: Relevance
“…Few studies have examined the physiological effect of mouth-breathing versus tracheostomy breathing. 15,16 Even fewer studies have examined the physiological effects of reduced-size tracheotomy tube or capped tube. Haberth€ ur et al 17 investigated the work of breathing in 10 tracheostomized, spontaneously breathing patients in the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have examined the physiological effect of mouth-breathing versus tracheostomy breathing. 15,16 Even fewer studies have examined the physiological effects of reduced-size tracheotomy tube or capped tube. Haberth€ ur et al 17 investigated the work of breathing in 10 tracheostomized, spontaneously breathing patients in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The APACHE II score of our study group was found to be significantly lower (15/35 vs. 16/35, P 5 0.027) than that of the control group. The difference of a single score point is not associated with a higher risk for morbidity or mortality because both scores are within the same subgroup (15)(16)(17)(18)(19), which predicts a 24% approximate mortality. 13 Our study group demonstrated a significantly shorter hospitalization period than the control group, following the decannulation process (5 vs. 20 days, P < 0.001), even though the general condition of the patients prior to and following decannulation (represented by the APACHE II and SOFA scores, respectively) was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Das Tracheostoma hilft, F den Sedierungsbedarf des Patienten zu reduzieren bzw. aufzuheben; F Traumatisierungen des Kehlkopfes und des NasenRachenRaums zu minimieren, F durch Reduzierung der Atemarbeit, der "resistance", des Spitzendrucks, des "intrinsic positive endexpiratory pressure" (intrinsic PEEP) und durch ein verbessertes Triggern des Beatmungs gerätes das "weaning" günstig zu beeinflussen [2,4,14,16]; F einen Wechsel zwischen assistierter Beatmung und reiner Spontanatmung (mit prolongierten Beatmungspausen) durchzuführen; F die Schluck und Kommunikationsrehabilitation des Patienten zu ermöglichen; F durch effiziente Bronchialtoilette bronchopulmonalen Infektionen vorzubeugen und F die Pflegbarkeit des NasenRachenRaums zu verbessern. …”
Section: Indikationenunclassified
“…The role of tracheostomy in this setting, however, has yet to be clearly defined. Tracheostomy has been shown to decrease the work of breathing [14], but this is not the issue in this scenario. Aspiration of oropharyngeal contents is common in neurologically impaired patients, but tracheostomy may not protect against aspiration [15].…”
Section: Con: Tracheostomy Is Not Ideal For Withdrawal Of Mechanical mentioning
confidence: 99%